2020
DOI: 10.1126/sciadv.aay0922
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase promotes DNA end processing by MRN and CtIP

Abstract: The repair of DNA double-strand breaks occurs through nonhomologous end joining or homologous recombination in vertebrate cells—a choice that is thought to be decided by a competition between DNA-dependent protein kinase (DNA-PK) and the Mre11/Rad50/Nbs1 (MRN) complex but is not well understood. Using ensemble biochemistry and single-molecule approaches, here, we show that the MRN complex is dependent on DNA-PK and phosphorylated CtIP to perform efficient processing and resection of DNA ends in physiological c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 56 publications
11
95
0
Order By: Relevance
“…The MRN complex, together with CtIP, competes with the main NHEJ factor DNA-PK. Recently, Deshpande et al ( 17 ) demonstrated, on the single DNA molecule level using DNA curtains, how CtIP and MRN can remove DNA-PK from DNA ends through endonucleolytic incision and hence channel repair from NHEJ to HR. Beyond HR, CtIP and MRN are also important for MMEJ, which mediates the joining of two DNA molecules with short microhomologies at the ends ( 18 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MRN complex, together with CtIP, competes with the main NHEJ factor DNA-PK. Recently, Deshpande et al ( 17 ) demonstrated, on the single DNA molecule level using DNA curtains, how CtIP and MRN can remove DNA-PK from DNA ends through endonucleolytic incision and hence channel repair from NHEJ to HR. Beyond HR, CtIP and MRN are also important for MMEJ, which mediates the joining of two DNA molecules with short microhomologies at the ends ( 18 ).…”
mentioning
confidence: 99%
“…While the mechanisms of nucleolytic resection by MRN and CtIP are becoming clearer ( 16 , 17 , 25 ), there is an important, nuclease-independent function of both MRN and CtIP in bridging and stabilizing DNA ends ( 26 28 ). Although DNA bridging is most likely critical to facilitate the catalytic functions in DSB repair by both end-joining and recombination, it remains poorly understood.…”
mentioning
confidence: 99%
“…We show here that ATM-dependent removal of DNA-PKcs is a prerequisite for the CtIP/MRE11 dependent Ku eviction from seDSBs. Experiments using purified human proteins have shown that DNA-PKcs mutated on the ABCDE cluster impairs stimulation of EXO1 by the MRN complex, comprising MRE11 ( 63 ) Recently, it was found that despite DNA-PKcs blocked with Ku at DNA ends greatly stimulates human MRE11-mediated inner incision on one strand in vitro , the yield of the second strand incision was much lower under these conditions ( 74 ). Together with our data, this suggests that DNA-PKcs release may be essential to permit the second incision on the other strand that is necessary for Ku release.…”
Section: Discussionmentioning
confidence: 99%
“…CDC45 plays a key role in late G1, as it is a key element of the DNA replication machinery; thus, it is deemed as a key element of the pathogenic network in CC [ 38 ]. Furthermore, DNA-PK, a dynamic enzyme involved in DNA double-stranded breaks repair pathway [ 39 ], has been proposed as a therapeutic target [ 40 , 41 ], while E2F1 plays critical roles in both cell cycle regulation and chromosome segregation. It has been reported that E2F1 may promote DNA replication and cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%